Japón 1941 : el camino a la infamia, Pearl Harbor - Hotta, Eri, 1971-; Urrutia, Belén; Hotta, Eri, 1971- (Barcelona : Galaxia Gutenberg, 2015)
Examines the attack on Pearl Harbor from the Japanese perspective.
Online resource; title from PDF title page (Digitalia, viewed December 15, 2016)
Keywords: World War, 1939-1945 -- Japan; Military planning -- Japan -- History -- 20th century; Japan -- Military policy; Japan -- Politics and government -- 1926-1945.; War -- Decision making; Pearl Harbor (Hawaii), Attack on, 1941.; Electronic books